Juan Carlos, escucha : primer balance de la España sin Franco / Pedro Calvo Hernando - González Márquez, Felipe (1942-) Tierno Galván, Enrique (1918-1986); Calvo Hernando, Pedro
Epílogo con opiniones de políticos y sindicalistas (p. 297-338 )